2014
DOI: 10.1002/ajhb.22574
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and lifestyle characteristics of active and inactive saudi and british adolescents

Abstract: significantly (p <0.001) associated with lower activity levels in both the Saudi and British adolescents. Having lower frequency of fruit intake was significantly (p <0.001) was associated with lower activity levels, whereas increased frequency of consumption of French fries/potato chips was significantly (p =0.008) associated with increased activity levels in Saudi adolescents. Among British adolescents, lower frequency of breakfast was (p = 0.045) associated with lower activity levels, increased frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Positive support for participation in physical activity mentioned in more than one study was the knowledge that physical activity is important [ 92 , 93 ] and desire to enhance one’s appearance [ 94 , 95 ]. Healthy diet, such as the consumption of fruits and vegetables, were also reported as positive correlates several studies [ 66 , 86 88 ].…”
Section: Resultsmentioning
confidence: 83%
“…Positive support for participation in physical activity mentioned in more than one study was the knowledge that physical activity is important [ 92 , 93 ] and desire to enhance one’s appearance [ 94 , 95 ]. Healthy diet, such as the consumption of fruits and vegetables, were also reported as positive correlates several studies [ 66 , 86 88 ].…”
Section: Resultsmentioning
confidence: 83%
“…[24] It is increasingly accepted that an accumulation of environmental, physiological, personal, and lifestyle factors throughout life play a major role in cardiovascular disease morbidity and mortality. [25] Studies concerning the dietary and lifestyle behaviors of students in the health career reported controversial results, but most of these studies indicated that the majority of these students have a high tendency to engage in unhealthy dietary and lifestyle habits including meal skipping, low fruits and vegetables intake, high fast food consumption, and minimal physical activity. [26][27][28] Analysis of the dietary habits of the students in the present sample revealed adoption of several undesired dietary habits.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that childhood obesity is increasing worldwide [ 37 ], with recent trends suggesting that the sharpest upsurges in prevalence are in the GCC countries [ 9 ]. It is increasingly accepted that an accumulation of environmental, physiological, personal and lifestyle factors throughout life play a major role in CVD morbidity and mortality [ 38 ]. The growing numbers of obese children and adolescents worldwide demand an investment in primary and secondary prevention of obesity and being overweight in youth [ 39 ].…”
Section: Discussionmentioning
confidence: 99%